An Analysis of the Top-cited Articles in Emergency Medicine Education Literature - Munzer, Brendan W. (West J Emerg Med, 2017)
INTRODUCTION: Dissemination of educational research is critical to improving medical education, promotion of faculty and ultimately patient care. The objective of this study was to identify the top 25 cited education articles in the emergency medicine (EM) literature and the top 25 cited EM education articles in all journals, as well as report on the characteristics of the articles. METHODS: Two searches were conducted in the Web of Science in June 2016 using a list of education-related search terms. We searched 19 EM journals for education articles as well as all other literature for EM education-related articles. Articles identified were reviewed for citation count, article type, journal, authors, and publication year. RESULTS: With regards to EM journals, the greatest number of articles were classified as articles/reviews, followed by research articles on topics such as deliberate practice (cited 266 times) and cognitive errors (cited 201 times). In contrast in the non-EM journals, research articles were predominant. Both searches found several simulation and ultrasound articles to be included. The most common EM journal was Academic Emergency Medicine (n = 18), and Academic Medicine was the most common non-EM journal (n=5). A reasonable number of articles included external funding sources (6 EM articles and 13 non-EM articles.) CONCLUSION: This study identified the most frequently cited medical education articles in the field of EM education, published in EM journals as well as all other journals indexed in Web of Science. The results identify impactful articles to medical education, providing a resource to educators while identifying trends that may be used to guide EM educational research and publishing efforts.